2007
DOI: 10.1063/1.2716344
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional nanoscale subsurface optical imaging of silicon circuits

Abstract: Three-dimensional subsurface imaging through the back side of a silicon flip chip is reported with a diffraction-limited lateral resolution of 166nm and an axial performance capable of resolving features only 100nm deep. This performance was achieved by implementing sample-scanned two-photon optical beam induced current microscopy using a silicon solid immersion lens and a peak detection algorithm. The excitation source was a 1530nm erbium:fiber laser, and the lateral optical resolution obtained corresponds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…The details of the prescription used to design the correct s-SIL for imaging at a given sub-surface depth have already been discussed. In a further analogy with two-photon fluorescence microscopy, we have also shown that the TOBIC effect can provide a means of generating ultra-high 2D and, in addition, 3D resolved imaging because the generation of significant photocurrent only occurs within one confocal parameter of the focused spot [2,21,67,68]. The results are illustrated in Figures 12-14 below.…”
Section: Solid Immersion Lens Microscopy Using Tobic Imagingmentioning
confidence: 77%
See 2 more Smart Citations
“…The details of the prescription used to design the correct s-SIL for imaging at a given sub-surface depth have already been discussed. In a further analogy with two-photon fluorescence microscopy, we have also shown that the TOBIC effect can provide a means of generating ultra-high 2D and, in addition, 3D resolved imaging because the generation of significant photocurrent only occurs within one confocal parameter of the focused spot [2,21,67,68]. The results are illustrated in Figures 12-14 below.…”
Section: Solid Immersion Lens Microscopy Using Tobic Imagingmentioning
confidence: 77%
“…We have investigated this optical lever effect in detail for both the h-SIL and the s-SIL [2,21], not only because it plays an extremely important role in the imaging system as a whole, but because it was suggested and confirmed that there is an optical lever effect in the axial direction as well -although initially the axial dependency was not fully understood [22]. We carried out a detailed analysis on both types of SIL, examining the optical lever effect in the axial and lateral directions by using the ray tracing software ASAP (Breault Research Organization).…”
Section: Magnification Effects In Solid Immersion Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…This need is evidenced by the recent development of schemes to image such features with increasing resolution [1], [2], [3], [4]. Here, we report a lateral resolution of 0.37µm (λ/3.24) while imaging subsurface features of an IC from the backside using a custom infrared widefield microscope and a numerical aperture increasing lens (NAIL).…”
Section: Introductionmentioning
confidence: 99%
“…A silicon NAIL placed on the backside of a silicon substrate effectively transforms the NAIL and the planar sample into an integrated SIL. This imaging scheme allows for high resolution backside imaging through the substrate of an IC which is often necessary because opaque interconnect metal layers hinder frontside optical microscopy [2], [3], [4]. Focusing under the high NA conditions provided by the NAIL enables us to observe the effects of polarization and dielectric interfaces in the focal region.…”
mentioning
confidence: 99%